2023
DOI: 10.4236/aim.2023.131001
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of the Global COVID-19 Pandemic and Invasive Fungal Pathogens in SARS-COV-2 Associations: A Dangerous Relationship

Abstract: Background: COVID-19 is a rapidly transmissible pneumonia-like illness caused by SARS-CoV-2 that out broke in China in 2019 and is currently circulating worldwide. In the current context of the SARS-CoV-2 pandemic, complications are observed in clinical settings for the treatment of severe COVID-19 disease in nosocomial settings, due to cases of fungal co-infections. Objective: To carry out a review on fungal infections associated with respiratory infections caused by COVID-19 (Sars-Cov-2) and their aggravatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Recent research has revealed that strains of A. flavus, the second largest cause and one of the main agents of serious comorbidities, including Aspergillosis; also causing co-infections in patients with severe infection by the SARS-CoV-2 virus, leading to pulmonary aspergillosis associated with COVID-19 (Mariscal et al, 2023;Simmons et al, 2023) were tested after exposure to the same azoles agricultural products had the MIC (Minimum Inhibitory Concentration) for drugs of the same class, posaconazole, voriconazole and itraconazole increased, showing that agricultural pesticides can, in fact, reduce the effectiveness of antifungals used in the clinic (Meireles et al, 2019).…”
Section: Isolation Of Filamentous Fungimentioning
confidence: 99%
“…Recent research has revealed that strains of A. flavus, the second largest cause and one of the main agents of serious comorbidities, including Aspergillosis; also causing co-infections in patients with severe infection by the SARS-CoV-2 virus, leading to pulmonary aspergillosis associated with COVID-19 (Mariscal et al, 2023;Simmons et al, 2023) were tested after exposure to the same azoles agricultural products had the MIC (Minimum Inhibitory Concentration) for drugs of the same class, posaconazole, voriconazole and itraconazole increased, showing that agricultural pesticides can, in fact, reduce the effectiveness of antifungals used in the clinic (Meireles et al, 2019).…”
Section: Isolation Of Filamentous Fungimentioning
confidence: 99%